The Influence of Practicum-Based Outdoor Inquiry Model on Science Process Skills in Learning Physics - Wardani, Yeni Ristya; Mundilarto, Mundilarto; Jumadi, Jumadi; Wilujeng, Insih; Kuswanto, Heru; Astuti, Dwi Puji (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2019)
The main purpose of this study is to find out the influence of practicum-based outdoor inquiry model on science process skills. Quasi-experiment design was employed as the research method by Matching Only Post-test Control Group. The research sample was taken using a cluster sampling technique. The samples consisted of experimental class (XI MIA 1) in a total of 25 students treated with practicum-based outdoor inquiry model. The control class (XI MIA 3) consisted of 29 students treated with direct instruction model. In collecting the data, essay test was used in the form of worksheets containing the aspect of science process skills of formulating hypotheses, designing experiment, interpreting data into tables, and drawing a conclusion (inferring). The study results demonstrate that practicum-based outdoor inquiry model was effective in improving the science process skills. It was shown in p-value (significant) of 0.00. The implication of this study is the need to design a practicum-based outdoor inquiry model by noticing what skills are going to improve by means of more varied outdoor activities.